2023
DOI: 10.3390/ijms242316556
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Involvement in Heart, Liver, and Lung Diseases—A Lesson from Cytokine Storm Syndrome

Cecilia Napodano,
Valeria Carnazzo,
Valerio Basile
et al.

Abstract: Inflammation and inflammasomes have been proposed as important regulators of the host–microorganism interaction, playing a key role in morbidity and mortality due to the coronavirus disease 2019 (COVID-19) in subjects with chronic conditions and compromised immune system. The inflammasome consists of a multiprotein complex that finely regulates the activation of caspase-1 and the production and secretion of potent pro-inflammatory cytokines such as IL-1β and IL-18. The pyrin containing NOD (nucleotide-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…These cytokines can stimulate chondrocytes to secrete fibrinolysins, directly or indirectly inducing an inflammatory response. 25 , 26 Therefore, effective strategies for the treatment of OA should focus on preventing and mitigating the effects of oxidative stress on chondrocytes and the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines can stimulate chondrocytes to secrete fibrinolysins, directly or indirectly inducing an inflammatory response. 25 , 26 Therefore, effective strategies for the treatment of OA should focus on preventing and mitigating the effects of oxidative stress on chondrocytes and the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-κB signaling induces the transcription of pro-IL-1β and NLRP3, which is essential for in ammasome activation [42]. NLRP3 is the most extensively studied in ammasome sensor in the heart [43],…”
Section: Discussionmentioning
confidence: 99%
“…It represents the advanced stage of various CVD, including myocarditis, MI, cardiomyopathy, hypertension, atrial fibrillation, valvular heart disease, alcohol abuse, and infection (Bracey et al, 2013). Recent studies on calcineurin transgene mice have shown elevated mRNA of NLRP3 and enhanced cleavage of caspase-1 along with cardiac hypertrophy and ventricular dilatation (Bracey et al, 2013;Napodano et al, 2023). Genetic ablation of NLRP3 or administration of IL-1 receptor antagonist has been found to attenuate cardiac inflammation and systolic dysfunction (Bracey et al, 2013;Zhang et al, 2014;Napodano et al, 2023).…”
Section: Exercise Affects Hf and Regulates Nlrp3 Inflammasomementioning
confidence: 99%
“…Recent studies on calcineurin transgene mice have shown elevated mRNA of NLRP3 and enhanced cleavage of caspase-1 along with cardiac hypertrophy and ventricular dilatation (Bracey et al, 2013;Napodano et al, 2023). Genetic ablation of NLRP3 or administration of IL-1 receptor antagonist has been found to attenuate cardiac inflammation and systolic dysfunction (Bracey et al, 2013;Zhang et al, 2014;Napodano et al, 2023). Additionally, activation of NLRP3 inflammasome has been observed in LPSstimulated cardiac fibroblasts and myofibroblasts, suggesting that its potential contribution to myocardial dysfunction through NLRP3 inflammasome or pyroptosis (Zhang et al, 2014;Boza et al, 2016).…”
Section: Exercise Affects Hf and Regulates Nlrp3 Inflammasomementioning
confidence: 99%